Changes in Soil Bacterial and Fungal Community Composition and Functional Groups During the Artificial Restoration of Degraded Grassland of “Black‐Soil Mountain” - Lele Xie; Yushou Ma; Yanlong Wang; Yuan Ma; Xiaoli Wang (Ecology and Evolution)
ABSTRACT About 35% of grassland in Sanjiangyuan area of China has degenerated into black‐soil mountain. Artificial grassland is considered to be an effective measure to alleviate the severely degraded grassland in the alpine region of the three rivers and has been widely used. However, the pattern, potential function, and changes of carbon and nitrogen contents of soil microorganisms in degraded grassland in Heimushan by planting artificial grassland are still unclear. In this study, mixed‐sown artificial alpine grassland (AG) was the focus of our study, whereas degraded black‐soil mountain grassland (BG) and natural alpine grassland (NG) served as controls. Illumina 16S and ITS gene sequence analyses were used to analyze the community structure of the soil bacteria and fungi. The functional groups of NG, AG, and BG were predicted using the FAPROTAX and FUNGuild databases. In addition, the levels of soil carbon, nitrogen, and soil enzyme activities were evaluated. The results indicated a significant increase in the aboveground biomass of BG due to the planting artificial grassland. Moreover, the contents of total carbon (TC), total nitrogen (TN), ammonium nitrogen (NH4+−N), microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), and leucine aminopeptidase (LAP) increased in the soil. Planting artificial grasslands changed the composition of bacterial and fungal communities. Among these, the bacterial community was more sensitive to planting artificial grasslands. The relative abundance of bacterial functional groups involved in carbon and nitrogen cycling changed significantly, suggesting that bacteria may play a role in regulating nutrient cycling during artificial grassland planting. Soil TC, TN, LAP, and NH4+−N affected the microbial community structure related to carbon and nitrogen. NH4+−N and β‐1,4‐glucosidase were carbon and nitrogen factors, respectively, that affected functional changes in fungi. These results indicate that planting artificial grasslands can effectively enhance the productivity of degraded black‐soil mountain and regulate soil microbial communities and soil physical and chemical properties.